Delayed Surgical Treatment for Long Onset Facial Paralysis. (23rd August 2013) - Rivas, Jose A.; Garcia, Laura; Forero, Victor H.; Rivas, Alejandro
Abstract : Objectives: Present qualitative evidence that supports surgical intervention to those patients with long onset facial paralysis. Methods: Retrospective study of clinical and surgical records of patients operated from July 2006 to September 2012. Twenty‐two patients with long onset facial paralysis were operated at a specialized center. Patients underwent surgical facial nerve decompression. Preoperatory and outcomes were recorded with the House‐Brackmann facial function score (HBs). Intraoperative stimulation response was obtained as indicator prognostic outcome for facial nerve function. Results: Patients who undergo surgical decompression obtain reduction in the HBs when intraoperative stimulation is obtained. Conclusions: Surgical decompression of the facial nerve is an option for subjects with long onset facial nerve paralysis with improvement of facial function through time.